Bernhard, Suffering, and the Value of Language1. (July 2014) - Rush, Fred
<x xml:space="preserve">Abstract</x> It is almost a truism to say that twentieth‐century philosophy has been concerned to a large degree with the question of the relation of language to meaning. Much of the concern has had to do with making more precise or more perspicuous the relation of language to thought and to the world. The twentieth century was also a time of immense human suffering, but the relation of suffering, as both a dimension of the world and as an aspect of thought, to its linguistic expression has received less philosophical attention. This paper forwards select works from across the writings of the Austrian novelist and dramatist Thomas Bernhard as investigations of these topics. In setting out and evaluating some of Bernhard's signal artistic considerations of the topic, I argue that understanding his work as a literary equivalent to Wittgenstein's more philosophical treatment of some of the same issues does not limn the deepest structure of Bernhard's thought—even though Bernhard often encourages this identification. Bernhard is even more pessimistic than Wittgenstein on a number of core issues; consideration of Bernhard's work in light of Schopenhauer—also a thinker important for Wittgenstein—is more revealing.